Muslim women from the margin to the text of the approach in the book of Abdul Salam Yasin enlightened believers - Albadrany, Abdalsatar A. (Humanities Journal of University of Zakho, 2013)
The importance of this approach of dealing with the book Mr. Abdessalam Yassine marked (enlighten believers) as a project instructive bioavailable actuation deduced from the culture of globalization or Allayikeh, which represents the same (draft instructive) works in the origin criteria on the absence of religious thought and the adoption of the mind, and so-called Balonsna; any deregulation of human Streptococcus that he believes in, And gives the right to critique (text) after historical material does not have any sanctity apart from other texts, they are if resistance for (power discourse), and thus worked on the separation of church and state, to achieve the same in the fields as a whole, economic, social and psychological, and because the world Product for this project did not want him to be confined in a narrow environment, transferred to the surrounding world as a culture irony aimed at undisclosed details to sabotage the cultures of the peoples in and out of her privacy; marginalized and even put their customs and beliefs in the trash. Mr. Yassin wants to come out of women and men; but Muslim youth in general from the slavery of jurisprudence Anahtati and characterization tools actors to achieve the dream of a world based on justice and charity bilateral . The culture of globalization, culture quality and vision of universality of man and life in all what holds D. life of meaning, which at the same time disruption of Iqinat institution in human thought, and produce new standards for dealing with space cognitive humanitarian who contributes to building the universe, outside of this globalization is the world in the nets heterogeneity, and a linear path, or proven act and Allatgayer, you can merge the world in geographic and cultural one away from the founder imagination in human memory.? Works professor Abdessalam Yassine in his book (enlighten believers) to reshape the visualization of local Besnfaha sacred and positive to establish a generation blaming memory Tasilah not allow one to open a loophole erase privacy or uniqueness, it's roots Altaeselah fixed, but its branches in the sky. It reframes The question that Antmr under visualization and invitations Almahih to the fact the purpose of faith, I mean a question of existence and re-activate the instinct, the mute, audio innate liquid about the meaning of existence and the fact my presence and very traffic from this life bizarre antics., then basic purpose of the book seeks to bring believers Aleghantat Abidat of bestiality Acquiesces and bonded any level of emancipation margin inattention to board fullness in the presence of God.